Evolution of the pseudogap state in HTSC single crystals ReBa₂Cu₃O₇₋δ (Re=Y, Ho) doped with Al and Pr - Vovk, R.V.; Zavgorodniy, A.A.; Obolenskii, M.A.; Samoilov, A.V.; Biletskiy, Y.V.; Pinto Simoes, V.M. (Functional Materials, 2009)
Studied has been the effect of oxygen deficiency as well as of a low (up to 5 %) Al and Pr doping on conductivity in the basis plane of the ReBa₂Cu₃O₇₋δ (Re=Y, Ho) HTSC single crystals. The excess conductivity Δσ(T) of the studied samples has been found to show an exponential character in a wide temperature range Tf<T<T*. The description of the excess conductivity as Δσ~(1-T/T*)exp(Δ*ab/T) can be interpreted within the frames of medium field theory where T* is the mean field temperature of superconducting transition. The temperature dependence of the pseudogap can be satisfactorily described in terms of the BCS-BEC crossover theoretical model. The oxygen content reduction and a low Al doping results in widening of the temperature interval where the PG mode is realized, thus narrowing the area of linear ρ(Т) dependence in the ab plane. A low Pr doping concentrations (z≈0.05) results in an unusual effect of a significant narrowing of temperature interval where the PG is realised, thus extending the linear ρ(Т) region. Досліджено вплив кисневого дефіциту, а також слабкого (до 5 %) допування алюмінієм і празеодимом на провідність у базисній площині ВТНП-монокристалів ReBa₂Cu₃O₇₋δ (Re=Y, Но). Встановлено, що надлишкова провідність Δσ(T) зразків у широкому інтервалі температур Tf<T<T* підпорядковується експоненціальній температурній залежності. При цьому опис надлишкової провідності за допомогою співвідношення Δσ~(1-T/T*)exp(Δ*ab/T) може бути інтерпретований у термінах теорії середнього поля, де T* представлена, як середньо польова температура надпровідного переходу, а температурна залежність псевдощілини задовільно описується у рамках теорії кросовера БКШ-БЕК. Зниження вмісту кисню і слабке легування алюмінієм приводить до ефекту розширення температурного інтервалу реалізації ПЩ-режиму, тим самим звужуючи область лінійної залежності ρ(Т) в аЬ-площині. Допування монокристалів YBaCuO малими домішками празеодиму z≈0.05 приводить до незвичайного ефекту звуження температурного інтервалу реалізації ПЩ-режиму, подовжуючи лінійну ділянку залежності ρab(Т). Исследовано влияние кислородного дефицита, а также слабого (до 5 %) допирования алюминием и празеодимом на проводимость в базисной плоскости ВТСП-монокристаллов ReBa₂Cu₃O₇₋δ (Re=Y, Но). Установлено, что избыточная проводимость Δσ(T) образцов в широком интервале температур Tf<T<T* подчиняется экспоненциальной температурной зависимости. При этом описание :избыточной проводимости посредством соотношения Δσ~(1-T/T*)exp(Δ*ab/T) может быть интерпретировано в терминах теории среднего поля, где T* представлена как среднеполевая температура сверхпроводящего перехода, а температурная зависимость псевдощели удовлетворительно описывается в рамках теории кроссовера БКШ-БЭК. Понижение содержания кислорода и слабое легирование алюминием приводит к эффекту расширения температурного интервала реализации ПЩ-режима, тем самым сужая область линейной зависимости ρ(Т) в аЬ-плоскост: и. Допирование монокристаллов YBaCuO малыми добавками празеодима z≈0.05 приводит к необычному эффекту сужения температурного интервала реализации ПЩ-режима, тем самым удлиняя линейный участок зависимости ρab(Т).